6G-enabled open-pit mine security: toward wise evaluation, monitoring, and early warning - Sun, Xiaokun; Shen, Honghao; Jiang, Tingting; Zhang, Peng; Peng, Simiao; Zhang, Shupeng (Frontiers in Earth Science, 2023)
The mining of open pit can easily cause geological disasters such as landslide and debris flow. It is widely acknowledged that communication technology could solve the existing problems in engineering practice from the aspects of disaster monitoring, deformation monitoring, landslide warning and emergency communication. This research paper introduces a fully integrated monitoring and early warning solution tailored for mining regions. By synergizing 6G and Global Navigation Satellite System (GNSS) technologies, the system effectively addresses signal transmission challenges in complex environments. The utilization of 6G’s high-speed, low-latency, and extensive connectivity capabilities enables efficient communication in these settings. The study focuses on a specific open-pit mine located in a cold region of China, utilizing it as a case study to demonstrate the system’s effectiveness in enhancing slope safety through comprehensive monitoring and early warning mechanisms. Apart from considering traditional dump characteristics and external factors, the system also introduces an innovative early warning index for detecting slope changes. Applying the Analytic Hierarchy Process (AHP) and Fuzzy comprehensive evaluation method ensures reliable evaluation results, facilitating slope assessment, monitoring, and early warning procedures in water-rich open-pit mines situated in cold areas.